Sosialisasi Manajemen Laktasi Pada Masa Pandemi Di Desa Pucung Kecamatan Balongpanggang Gresik - Yurilla Endah Muliatie; Nur Jannah (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
Lactation is the process of giving breast milk (ASI) to babies. Currently, Mother's awareness of the importance of lactation has begun to build. Babies who need growth and development are an asset for future generations, therefore healthy foods that contain nutrients are needed, all of which start with a healthy life. The existence of the Covid-19 Pandemic presents an obstacle for breastfeeding mothers where they cannot carry out Posyandu activities because the services are eliminated during the pandemic period. And because of the lack of information about the Covid-19 Virus in the village, which is sometimes constrained by signals, power outages and physical distancing that prevented them from accessing the information at the village health Posyandu, therefore socialization was given through the Village Health Posyandu Coordinator (Poskesdes) so hopefully the Breastfeeding mothers can find out how effective Lactation management is during the Covid-19 pandemic. The socialization that can be carried out is by distributing pamphlets through the Poskesdes Coordinator and creating an online communication network to record breastfeeding mothers so that they can find out their condition and are expected to respond quickly if someone is affected by the Covid-19 Virus. With this kind of management, it can finally help the government to reduce the prevention of Covid-19 in breastfeeding mothers so as to create a healthy and smart generation for Indonesian children.